2023
DOI: 10.1109/tnnls.2022.3158867
|View full text |Cite
|
Sign up to set email alerts
|

Robust Peak Detection for Holter ECGs by Self-Organized Operational Neural Networks

Abstract: Although numerous R-peak detectors have been proposed in the literature, their robustness and performance levels may significantly deteriorate in low-quality and noisy signals acquired from mobile electrocardiogram (ECG) sensors, such as Holter monitors. Recently, this issue has been addressed by deep 1-D convolutional neural networks (CNNs) that have achieved state-of-the-art performance levels in Holter monitors; however, they pose a high complexity level that requires special parallelized hardware setup for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Duraj et al showed high performance on LUDB by incorporating the residual and squeeze-excitation blocks into the 1D U-Net architecture for extracting segments, such as P-waves, QRS complexes, and T-waves, regardless of the lead [ 88 ]. Gabbouj et al proposed a 1D self-organized operational neural network (ONN), evaluated on second CPSC, and achieved recall of 99.79%, precision of 98.42%, and F1-score of 99.10% [ 24 , 89 ]. However, during the training phase, it featured a high complexity in the number of multiply–accumulate operations and the number of parameters compared with 1D CNN architectures.…”
Section: Related Workmentioning
confidence: 99%
“…Duraj et al showed high performance on LUDB by incorporating the residual and squeeze-excitation blocks into the 1D U-Net architecture for extracting segments, such as P-waves, QRS complexes, and T-waves, regardless of the lead [ 88 ]. Gabbouj et al proposed a 1D self-organized operational neural network (ONN), evaluated on second CPSC, and achieved recall of 99.79%, precision of 98.42%, and F1-score of 99.10% [ 24 , 89 ]. However, during the training phase, it featured a high complexity in the number of multiply–accumulate operations and the number of parameters compared with 1D CNN architectures.…”
Section: Related Workmentioning
confidence: 99%
“…For example, in [5], a Holter system for monitoring the state of the heart based on the Zigbee method was developed, which has a measuring and recording device. In another work [6], a method for detecting peaks for Holter devices using self-organizing operational neural networks is presented. Also, Holter has a number of other names: outpatient ECS monitoring, longterm ECS monitoring, 24-hour ECS monitoring.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Different solutions are used for real-time monitoring on wearable devices, of which LSTM is also the most common (Amirshahi and Hashemi 2019, Saadatnejad et al 2020, Wójcikowski 2021, Gabbouj et al 2022. The same network was used as a basis for this study and was proven to be sufficient for real-time analysis on wearable devices (Amirshahi and Hashemi 2019, Wójcikowski 2021, Gabbouj et al 2022. Also, the 2020 PhysioNet/Computing in Cardiology Challenge showed that the most common solutions used for 12-lead classification were also CNNs and RNNs (Alday et al 2021).…”
Section: Introductionmentioning
confidence: 98%
“…In that field, one of the most commonly used classifiers is the Long Storm-term Memory (LSTM) network (Warrick et al 2020). Different solutions are used for real-time monitoring on wearable devices, of which LSTM is also the most common (Amirshahi and Hashemi 2019, Saadatnejad et al 2020, Wójcikowski 2021, Gabbouj et al 2022. The same network was used as a basis for this study and was proven to be sufficient for real-time analysis on wearable devices (Amirshahi and Hashemi 2019, Wójcikowski 2021, Gabbouj et al 2022.…”
Section: Introductionmentioning
confidence: 99%